Pelatihan Penggunaan Aplikasi Quizizz Sebagai Alternatif Media Evaluasi Pembelajaran Jarak Jauh - E Eddy; Ari Usman; Haida Dafitri (Jurnal TUNAS, 2021)
The government has taken various policies to prevent the spread of the Covid-19 virus. Among them: working from home, physical distancing, health protocols, large-scale social restrictions, and imposing restrictions on community activities. In the education sector, the Ministry of Education and Culture has made a face-to-face learning policy that has been transformed into distance learning, both online and offline. This applies from elementary to higher education. The learning process is a unity that can not be separated with the learning evaluation. Therefore the teacher must be able to determine what kind of evaluation model is suitable for use with their students in distance learning. Currently, there are quite a lot of applications that can be used for learning evaluation, one of which is quizizz. Considering that this quizizz application is interactive and internet-based, training needs to be done in its use. For that purpose, this training activity was carried out with the participants being teachers of the Harapan 3 Private Elementary School in Medan.